Indonesian Stock’s Influencer Phenomenon: Did Financial Literacy on Millennial Age Reduce Herding Behavior? - Ananda Chairunnisa; Zuliani Dalimunthe (Institute of Research and Community Outreach - Petra Christian University, 2021)
In Indonesia's capital market, there was a phenomenon that famous influencers seem to lead to behavioral bias in the stock market. The stock price changed significantly after those stock influencers shared information or recommended certain stocks. This research examined how the stock influencer's credibility affected investors' investment in recommended stock. We collected data from 132 individual investors who participated in the research. We used a questionnaire with a 5-Likert scale. The result showed that an influencer's credibility had a significant influence on investors' herding behavior. However, there was no significant evidence that financial literacy matters in that relationship. Interestingly, we found there was no significant difference in herding behavior between millennial and non-millennial investors.